Managing Director's Action Plan to the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2011)
The risks ahead and the role of the Fund. Global growth is flagging. In the advanced country core of the international monetary system, fiscal and financial vulnerabilities and uncertain growth prospects are feeding on each other, posing instability risks to a world with diminished policy buffers. The Fund's policy advice on tackling this situation is outlined in the Consolidated Multilateral Surveillance report. While responsibility of implementing the right policies lies with members, the Fund has a responsibility to help--by working out specifics, and finding and coordinating global solutions to immediate threats to global stability. At the same time, we cannot lose sight of the longer-term structural issues in the international monetary system, where at least visible progress if not closure is needed.